Higher waist circumference is associated with increased likelihood of female infertility: NHANES 2017-2020 results - Yin, Ying-Hua; Zhou, Su-Yu; Lu, Dong-Fang; Chen, Xiu-Ping; Liu, Bo; Lu, Shan; Han, Xiao-Dong; Wu, Ai-Hua (Frontiers in Endocrinology, 2023)
BACKGROUND: Waist circumference can be used as an anthropometric measure to assess central obesity and is easier and more convenient than the waist-to-hip ratio in identifying the risk of obesity and medical problems (1). Most studies showing an association between obesity and infertility in women have used BMI to measure obesity. Our goal was to examine any potential association between waist circumference and infertility. METHODS: This cross-sectional study, which formed part of the National Health and Nutrition Examination Survey (NHANES), comprised women ages 18 to 45 between 2017 and 2020. Participants without waist circumference data or information on infertility were removed from the study. The independent relationship between waist circumference and infertility was investigated using weighted binary logistic regression and subgroup analysis. RESULTS: We investigated 1509 participants and discovered that the prevalence of infertility rose as the WC trisection rose. (tertile 1, 7.55%; tertile 2,10.56%; tertile 3, 15.28%; trend < 0.001). Multivariate logistic regression showed that after total adjustment, higher WC levels were associated with an increased likelihood of infertility in women (OR1.02; 95% CI 1.01-1.03), and There was a 2% rise in the incidence of infertility for every unit (cm) increased WC. Subgroup analysis and interaction tests showed no significant dependence of the effects of marital status, diabetes, hypertension, and high cholesterol on the association between WC and infertility (p for all interaction tests > 0.05). The inflection point of the positive non-linear relationship between WC and infertility was 116.6 cm. Conclusion: Excessive waist circumference assessment may increase the probability of infertility, and more attention should be paid to the management of waist circumference should be given more attention.